Exigências de energia metabolizável para frangas de postura de 1 a 18 semanas de idade - Silva, Rosemeire da; Sakomura, Nilva Kazue; Resende, Kleber Tomás de [UNESP]; Basaglia, Roberta; Ariki, Joji (My University, 1997)
The trials were conduced to determine the energy requirements of growing pullets from 1 to 18 weeks of age,by means of the factorial method, using the comparative slaughter technique. The energy requirements for maintenance were determined utilizing the following feeding levels: ad libitum, 80% and 60% of ad libitum and sufficient for maintenance. Heat production was determined as a function of metabolizable energy intake (MEI) and the retained energy, which, when extrapolated to zero of ME intake, indicated net energy (NE) for maintenance of 63.6; 71.24 and 76.78 kcal/kg0.75/day, for the periods from 1 to 6, 7 to 12 and 13 to 18 weeks of age, respectively. ME requirements for maintenance were determined by ME intake regression as a function of the retained energy, which, when extrapolated to zero retained energy, resulted in 86.12; 98.95 and 116.24 kcal/kg0.75 per day for the periods from 1 to 6, 7 to 12 and 13 to 18 weeks of age, respectively. ME requirements for weight gain were determined through regression analysis of the energy present in the body as a function of body weight, obtained by means of weekly slaughtering during the period from 1 to 18 weeks old. The regression coefficients of energy present in the body as a function of the body weight were used for the determination of the NE requirements for gain. By taking into account the conversion efficiencies of ME to NE for gain, the requirements for weight gain were: 4.11, 5.78 and 7.32 kcal/g ME for the periods 1 to 6, 7 to 12, and 12 to 18 weeks of age, respectively.
Metabolizable energy requirements for hen pullets from 1 to 18 weeks of age
Keywords: Comparative slaughter; Energy requirements; Equation of prediction; Heat prodution; Pullets